2017
DOI: 10.1002/cjce.23034
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of four petrologic end members from Alberta oil sands and comparison between different mines and sampling times

Abstract: The current research was performed on four petrologic end members samples from Syncrude's North Mine collected in 2012 (NM12), i.e. marine clay (MC), marine sand (MS), estuarine clay (EC), and estuarine sand (ES). The mineralogical compositions of the four petrological end members were determined using X-ray diffraction (XRD), quantitative XRD (QXRD), elemental analysis, and particle size distribution (PSD) measurements.Bulk samples from the four petrologic end members, after bitumen removal, were mainly compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 57 publications
4
13
1
Order By: Relevance
“…In addition, to judge the relative abundance of mineral compositions in the original end members and SFS, the results of mineral composition of SFS reported in Table for each end member compared with the original samples (bulk and different size fractions) of the same petrological end members (NM12 data from Geramian et al) are plotted in ternary diagrams (Figure ). The comparison indicated a correlation among the mineral composition of SFS and the original samples.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, to judge the relative abundance of mineral compositions in the original end members and SFS, the results of mineral composition of SFS reported in Table for each end member compared with the original samples (bulk and different size fractions) of the same petrological end members (NM12 data from Geramian et al) are plotted in ternary diagrams (Figure ). The comparison indicated a correlation among the mineral composition of SFS and the original samples.…”
Section: Discussionmentioning
confidence: 99%
“…It can be speculated that a very clean supernatant collected from EC samples is related to bitumen, clay minerals, TOC, and water contents. In the previous study by Geramian et al, the bulk samples of the same petrologic end members were characterized . The authors reported that bulk sample of EC consisted of the lowest amount of bitumen (< 0.1 wt%), the highest clay minerals content (32.4 wt%, swelling and non‐swelling clays), the lowest TOC content (0.06 wt%) and the second highest water content (7.1 wt%) compared with other end members.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations